The Catch of Mackerel (Euthynnus affinis) in Relation to Oceanographic Conditions in Bulukumba Waters, Flores Sea - Safruddin; Fajar Hidayat Fajar; Mukti Zainuddin (Hasanuddin University, 2024)
This study aims to describe the relationship between mackerel (Euthynnus affinis) catch and oceanographic conditions in the Flores Sea. This research was conducted from September to December 2020 in the waters of Bulukumba, Flores Sea. This research uses two methods: collecting primary data on tuna catches and geographic points; measuring parameters of Sea Surface Temperature (SST), chlorophyll-a, and salinity; and collecting secondary data in the form of satellite imagery of Sea Surface Temperature (SST) and chlorophyll-a and salinity obtained from several sites. Data analysis was carried out using multiple regression analysis and spatial analyst techniques. The results showed significant effects of SST parameters, chlorophyll-a, and salinity on tuna catch (p < 0.1).